Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area. (May 2023) - Huang, Di; Gao, Lirong; Zhu, Shuai; Qiao, Lin; Liu, Yang; Ai, Qiaofeng; Xu, Chi; Wang, Wenwen; Lu, Meiling; Zheng, Minghui
Abstract: Organochlorine pesticides show biological toxicity and their degradation typically takes many years. Previous studies of agrochemical-contaminated areas have mainly focused on limited target compounds, and emerging pollutants in soil have been overlooked. In this study, we collected soil samples from an abandoned agrochemical-contaminated area. Target analysis and non-target suspect screening by gas chromatography coupled with time-of-flight mass spectrometry were combined for qualitative and quantitative analysis of organochlorine pollutants. Target analysis showed that dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyldichloroethylene (DDE), and dichlorodiphenyldichloroethane (DDD) were the main pollutants. With concentrations between 3.96 × 10 6 and 1.38 × 10 7 ng/g, these compounds posed significant health risks at the contaminated site. Non-target suspect screening identified 126 organochlorine compounds, most of which were chlorinated hydrocarbons and 90% of the compounds contained a benzene ring structure. The possible transformation pathways of DDT were inferred from proven pathways and the compounds identified by non-target suspect screening that had similar structures to DDT. This study will be useful for studies of the degradation mechanism of DDT. Semi-quantitative and hierarchical cluster analysis of compounds in soil showed that the distribution of contaminants in soil was influenced by the types of pollution sources and distance to them. Twenty-two contaminants were found in the soil at relatively high concentrations. The toxicities of 17 of these compounds are currently not known. These results improve our understanding of the environmental behavior of organochlorine contaminants in soil and are useful for further risk assessments of agrochemical-contaminated areas. Graphical abstract: Image 1 Highlights: Non-target and target analyses were combined for identification of organochlorines. Carcinogenic risk and hazard quotients of the organochlorines were assessed. Possible transformation pathways of dichlorodiphenyltrichloroethane were inferred. Semi-quantitative analysis identified 22 pollutants with concentrations >100 ng/g.